Impact of Exercise on Type 2 Diabetes Mellitus: A Comprehensive Review - Rehab Abdullah Yahia et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and hyperglycemia, often accompanied by obesity and cardiovascular complications. Lifestyle interventions, particularly exercise, have proven to be effective in managing T2DM by improving glycemic control, enhancing insulin sensitivity, and reducing cardiovascular risk factors. This review examines the impact of different types of exercise—such as aerobic, resistance, and high-intensity interval training (HIIT)—on glycemic control and metabolic health in individuals with T2DM. The review also explores the mechanisms underlying these benefits and discusses challenges in adherence and future directions for integrating exercise into diabetes care. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/256 https://doi.org/10.5281/zenodo.14251341